At the violet hour modernism and violence in England and Ireland - Cole, Sarah (New York ; Oxford : Oxford University Press, 2012)
'At The Violet Hour' offers a richly historicised, trenchant look at the interlocking of literature with violence in British and Irish modernist texts.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Violence in literature; English literature -- 20th century -- History and criticism; English literature -- Irish authors -- History and criticism; Modernism (Literature) -- Great Britain